2007
DOI: 10.1523/jneurosci.2162-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Sodium Current in Purkinje Neurons from NaV1.1 Mutant Mice: Implications for Ataxia in Severe Myoclonic Epilepsy in Infancy

Abstract: Loss-of-function mutations of Na V 1.1 channels cause severe myoclonic epilepsy in infancy (SMEI), which is accompanied by severe ataxia that contributes substantially to functional impairment and premature deaths. Mutant mice lacking Na V 1.1 channels provide a genetic model for SMEI, exhibiting severe seizures and premature death on postnatal day 15. Behavioral assessment indicated severe motor deficits in mutant mice, including irregularity of stride length during locomotion, impaired motor reflexes in gras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
251
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(271 citation statements)
references
References 50 publications
15
251
3
Order By: Relevance
“…Moreover, GABAergic interneurons in the hippocampus have a profound and selective loss of sodium current and electrical excitability in global loss-of-function mouse models of DS (14,17). However, studies of other GABAergic inhibitory neurons in the cerebellum, reticular nucleus of the thalamus, and cerebral cortex have revealed smaller losses of sodium currents and lesser impairments of excitability in our mouse model of DS (16,18,19). Therefore, these previous observations did not establish a causal relationship between the loss of sodium current and action potential firing in GABAergic interneurons and the hyperexcitability, seizure, and premature death in DS.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Moreover, GABAergic interneurons in the hippocampus have a profound and selective loss of sodium current and electrical excitability in global loss-of-function mouse models of DS (14,17). However, studies of other GABAergic inhibitory neurons in the cerebellum, reticular nucleus of the thalamus, and cerebral cortex have revealed smaller losses of sodium currents and lesser impairments of excitability in our mouse model of DS (16,18,19). Therefore, these previous observations did not establish a causal relationship between the loss of sodium current and action potential firing in GABAergic interneurons and the hyperexcitability, seizure, and premature death in DS.…”
Section: Discussionmentioning
confidence: 86%
“…These global heterozygous mice exhibit temperature-induced and spontaneous seizures, mild ataxia, and premature death (14)(15)(16). Na V 1.1 channels are expressed in both excitatory and inhibitory neurons (3,6), yet electrophysiological studies in dissociated hippocampal neurons from DS mice showed selective loss of sodium current and excitability in GABAergic interneurons (14,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Scn1a +/− mice are a genetic model for a devastating form of epilepsy, severe myoclonic epilepsy of infancy (SMEI) (15-17). Loss of firing of GABAergic neurons and the resulting disinhibition of neural circuits are hypothesized to be the underlying cause of epilepsy and comorbid ataxia in this disease (13,14,18). Homozygous Scn1a −/− mice are more severely impaired and die on postnatal day 15 (P15) (13).…”
mentioning
confidence: 99%
“…Recordings of cerebellar Purkinje neurons from mutant mice showed a reduction of sodium currents without any change in the kinetics or voltage dependence of channel activation or inactivation. These changes were responsible for a reduction of the firing rates [141].…”
Section: Models Of Dravet Syndromementioning
confidence: 99%